1991
DOI: 10.1093/brain/114.2.867
|View full text |Cite
|
Sign up to set email alerts
|

Sural Nerve Morphometry in Diabetic Autonomic and Painful Sensory Neuropathy

Abstract: Observations have been made on a selected series of insulin-dependent patients with neuropathy, subdivided into three groups: (1) severe autonomic neuropathy with an accompanying painless sensory neuropathy; (2) severe autonomic neuropathy with a chronic painful sensory neuropathy; and (3) chronic or acute painful sensory neuropathy with no autonomic neuropathy. All three groups showed a loss of large and small myelinated nerve fibres in sural nerve biopsy specimens which was greater in Groups 1 and 2. Regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
88
3
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 0 publications
13
88
3
5
Order By: Relevance
“…In accord with the distal dominance of symptoms and signs, the longitudinal gradient of fiber loss along lower extremity nerve trunks is also directed from distal (where it is most severe) to proximal 4, 5, 6, 7, 9. Such a distally marked reduction in fiber density appears not only in sural nerve biopsies, but also in skin punch biopsies, which reveal the density of cutaneous innervation by small fibers (intraepidermal nerve fiber density; IENF).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In accord with the distal dominance of symptoms and signs, the longitudinal gradient of fiber loss along lower extremity nerve trunks is also directed from distal (where it is most severe) to proximal 4, 5, 6, 7, 9. Such a distally marked reduction in fiber density appears not only in sural nerve biopsies, but also in skin punch biopsies, which reveal the density of cutaneous innervation by small fibers (intraepidermal nerve fiber density; IENF).…”
Section: Discussionmentioning
confidence: 95%
“…It is generally agreed that fiber loss in lower extremity peripheral nerves is the most prominent histological fingerprint of DPN and involves large myelinated and/or small fibers 3, 4, 5, 6, 7, 8, 9. In accord with the distal dominance of symptoms and signs, the longitudinal gradient of fiber loss along lower extremity nerve trunks is also directed from distal (where it is most severe) to proximal 4, 5, 6, 7, 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in nerve conduction velocity and amplitude have been considered to reflect underlying structural pathology of the myelinated fibres [30]. Such pathology includes demyelination and a significant loss of myelinated fibres due to axonal degeneration [9,10]. In addition axonal atrophy and axo-glial dysjunction have also been demonstrated in some [31,32] but not in other [20,21,33] studies.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed neurophysiological studies in diabetic patients have shown that demyelination precedes axonal loss and that the latter may be responsible for the symptoms [8]. Whilst studies in patients with established neuropathy demonstrate a combination of demyelination and axonal degeneration of myelinated fibres and degeneration with regeneration of unmyelinated fibres [9][10][11] and endoneurial microangiopathy [12][13][14][15], the early pathological features of patients with diabetic neuropathy are not clearly defined.…”
Section: Introductionmentioning
confidence: 99%